2016
DOI: 10.1016/j.jns.2016.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition and relapse risk in pediatric MS: A pilot study

Abstract: We explored the association between baseline gut microbiota (16S rRNA biomarker sequencing of stool samples) in 17 relapsing-remitting pediatric MS cases and risk of relapse over a mean 19.8 months follow-up. From the Kaplan-Meier curve, 25% relapsed within an estimated 166 days from baseline. A shorter time to relapse was associated with Fusobacteria depletion (p=0.001 log-rank test), expansion of the Firmicutes (p=0.003), and presence of the Archaea Euryarchaeota (p=0.037). After covariate adjustments for ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 14 publications
6
118
1
1
Order By: Relevance
“…Similar modest differences, are reported in other autoimmune disease and are suggestive of ongoing inflammation (12,13). Further, gut microbiota composition has also been associated with relapse risk in paediatric MS (11). Larger, longitudinal studies are needed to better understand potential confounders, from comorbidity to concomitant medications.…”
supporting
confidence: 55%
“…Similar modest differences, are reported in other autoimmune disease and are suggestive of ongoing inflammation (12,13). Further, gut microbiota composition has also been associated with relapse risk in paediatric MS (11). Larger, longitudinal studies are needed to better understand potential confounders, from comorbidity to concomitant medications.…”
supporting
confidence: 55%
“…Stool samples were available from 17 of the 82 cases in the discovery set 28. We extracted and amplified DNA from stool samples and performed 16S rRNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…However, using the relapsing-remitting mouse model of spontaneously developing experimental autoimmune encephalomyelitis, it has been shown that the commensal gut flora -in the absence of pathogenic agents -is essential in triggering immune processes, leading to a relapsing-remitting autoimmune disease driven by myelin-specific CD4 + T cells. 81,82 Further research is now ongoing to determine the composition of the intestinal microbiota associated with an increased susceptibility to MS, 83,84 in addition to disease outcomes in those already with MS, 85 and this research may provide a conceptual basis for exploring new, less invasive treatment strategies.…”
Section: Implications For Patient Carementioning
confidence: 99%